1991
DOI: 10.1128/aac.35.9.1919
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Staphylococcus species and subspecies to teicoplanin

Abstract: Twenty-four Staphylococcus species and their subspecies were examined for their susceptibilities to teicoplanin by disk diffusion (30-,ug disk) and agar dilution for the determination of MICs. Moderately susceptible and resistant clinical strains were further tested for their susceptibilities to oxacillin and vancomycin. Teicoplanin resistance was not observed in the reference strains of the various Staphylococcus species isolated from healthy volunteers or animals. However, the novobiocin-resistant species St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 11 publications
1
16
0
2
Order By: Relevance
“…One possible approach that has received little attention and needs more research is the use of imipenem disks to determine vancomycin-resistant subpopulations. Schwalbe et al (277) found that S. haemolyticus strains selected by their growth on brain heart infusion agar containing 12 Decreased susceptibility of strains of S. haemolyticus and S. epidermidis to another glycopeptide, teicoplanin, has been more prevalent than that found with vancomycin (20,109,161,197). When determining the breakpoints of resistance and susceptibility, several groups have expressed concern over their inability to correlate results (47,119,197).…”
Section: Conventional Methodsmentioning
confidence: 99%
“…One possible approach that has received little attention and needs more research is the use of imipenem disks to determine vancomycin-resistant subpopulations. Schwalbe et al (277) found that S. haemolyticus strains selected by their growth on brain heart infusion agar containing 12 Decreased susceptibility of strains of S. haemolyticus and S. epidermidis to another glycopeptide, teicoplanin, has been more prevalent than that found with vancomycin (20,109,161,197). When determining the breakpoints of resistance and susceptibility, several groups have expressed concern over their inability to correlate results (47,119,197).…”
Section: Conventional Methodsmentioning
confidence: 99%
“…In contrast, 78% of selected S. epidermidis isolates from Hungary, Spain, and Switzerland were trimethoprim resistant, but the majority (70%) of these isolates were methicillin susceptible (19 ,ug/ml) in one study (14). Both vancomycin and teicoplanin resistance can be easily selected in vitro in S. haemolyticus by exposure of isolates to either vancomycin or teicoplanin (56,65), yet only teicoplanin resistance can be generated for S. epidermidis by stepwise exposure of this species to glycopeptides (17).…”
Section: Trimethoprimmentioning
confidence: 99%
“…It was suggested that S. haemolyticus is unique amongst CNS and especially predisposed to resistance to glycopeptides, because of its extraordinary genome plasticity and tendency to frequent DNA rearrangements (Takeuchi et al, 2005). According to various studies, the percentage of hospital-isolated S. haemolyticus strains with reduced susceptibility to teicoplanin is increasing (Bannerman et al, 1991;Cercenado et al, 1996;Goldstein et al, 1990). What is alarming is that the strains were also isolated from infants in neonatal intensive care units (Pereira et al, 2014).…”
Section: Resistance Of S Haemolyticus To the Last-chance Antimicrobimentioning
confidence: 99%